2007
DOI: 10.1002/cphc.200700197
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Calculation of the Potential of Mean Force for a Cation–π Complex in Water

Abstract: We report potential of mean force (PMF) calculations on the interaction between the p-sulfonatocalix[4]arene and a monovalent cation (Cs(+)). It has been recently shown from microcalorimetry and (133)Cs NMR experiments that the association with Cs(+) is governed by favourable cation-pi interactions and is characterized by the insertion of the cation into the cavity of the macrocycle. We show that the PMF calculation based upon a classical model is not able to reproduce both the thermodynamic properties of asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
(97 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, the thermodynamic parameters of complexation (Δ r H ° ≪ 0 and T Δ r S ° < 0 or ≈0) were in sharp contrast with those observed with multivalent cations, the process being totally enthalpy-controlled, and led to the conclusion that the monovalent metal cations bind inside the cavity where they can interact with the π-electrons of the phenyl groups of the calixarene. The inclusion of Cs + was confirmed by 133 Cs pulsed-gradient spin echo diffusion data and by a numerical approach combining molecular mechanics and DFT calculations …”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, the thermodynamic parameters of complexation (Δ r H ° ≪ 0 and T Δ r S ° < 0 or ≈0) were in sharp contrast with those observed with multivalent cations, the process being totally enthalpy-controlled, and led to the conclusion that the monovalent metal cations bind inside the cavity where they can interact with the π-electrons of the phenyl groups of the calixarene. The inclusion of Cs + was confirmed by 133 Cs pulsed-gradient spin echo diffusion data and by a numerical approach combining molecular mechanics and DFT calculations …”
Section: Introductionmentioning
confidence: 91%
“…The inclusion of Cs + was confirmed by 133 Cs pulsed-gradient spin echo diffusion data 5 and by a numerical approach combining molecular mechanics and DFT calculations. 6 In a previous study, we have shown by paramagnetic induced carbon-13 spin relaxation that the two monovalent cations, cesium and thallium, when complexed by the p-sulfonatocalix [4]arene, are well inside the cavity, approximately at similar locations, but with, apparently, a greater mobility for thallium. 7 Here, we are able to proceed with samples devoid of paramagnetic impurities to measure calixarene carbon-13 and proton longitudinal relaxation times (T 1 ) at two different values of the static magnetic field.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…11 Adoptions thereof were developed to investigate protein-protein interactions, 12 complexation, 13 adsorption, [14][15][16][17] or reaction rates. 11 Adoptions thereof were developed to investigate protein-protein interactions, 12 complexation, 13 adsorption, [14][15][16][17] or reaction rates.…”
Section: Theorymentioning
confidence: 99%
“…1 This was confirmed, as far as the Cs + -SC4 complex is concerned, by 133 Cs pulsedgradient spin echo diffusion data 2 and also by molecular mechanics coupled with density functional theory (DFT) calculations. 7 Although those previous works strongly suggested the inclusion of the monovalent metal cation within the calixarene cavity, they could not confirm unambiguously the exact location of the guest. In the present work, we intend to locate experimentally the metal cation by looking at the spin relaxation of nuclei belonging to the calixarene itself.…”
Section: Introductionmentioning
confidence: 84%